Video Q&A: Patients leading the direction of clinical research - an interview with Paul Wicks - Wicks, Paul (BioMed Central, 2014)
In this video Q&A, we talk to Paul Wicks about the emergence of participant-led research, and discuss how this field may be expected to develop in the near future, particularly with regard to personalized medicine.